2011
DOI: 10.1152/physiol.00052.2010
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Exercise: Endothelial Adaptations Beyond Active Muscle Beds

Abstract: Endothelial adaptations to exercise training are not exclusively conferred within the active muscle beds. Herein, we summarize key studies that have evaluated the impact of chronic exercise on the endothelium of vasculatures perfusing nonworking skeletal muscle, brain, viscera, and skin, concluding with discussion of potential mechanisms driving these endothelial adaptations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
168
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 209 publications
(367 reference statements)
8
168
2
3
Order By: Relevance
“…48 Existing evidence also suggests that physical activity exerts a protective effect on cognitive function. 49 The mechanisms underlying the protective effects of exercise in the cerebral circulation and neuronal tissue are largely unknown.…”
Section: Effects Of Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…48 Existing evidence also suggests that physical activity exerts a protective effect on cognitive function. 49 The mechanisms underlying the protective effects of exercise in the cerebral circulation and neuronal tissue are largely unknown.…”
Section: Effects Of Agingmentioning
confidence: 99%
“…Exercise-induced increase in the shear stress imposed on the endothelium by circulating blood is a well-established stimulus responsible for the upregulation of eNOS and increased local production of NO. 48 Despite strong autoregulation designed to maintain constant blood flow in the brain during changes in arterial blood pressure, existing evidence indicates that blood flow is increased in some regions of the brain during physical activity. 48 Indeed, increased blood flow in the motor and sensory cortex, as well as the cerebellum, is the result of an exerciseinduced increase in neuronal activity and subsequent vasodilatation caused by neurovascular coupling.…”
Section: Effects Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It is possible that the protocol used in this study, in terms of intensity or muscle mass, did not reach a threshold for hemodynamic forces and/or circulating factors that would result in a hyperemic response in leg muscles. Although a more intense ACE protocol could have increased blood perfusion of VL in SCI, the adherence to such an intensive exercise program would have been uncertain.…”
Section: Muscle Perfusion During Arm Exercisementioning
confidence: 96%
“…Indeed, animal studies have shown that exercise training induces vascular adaptations in skeletal muscles even without elevations in blood flow or metabolism. 16 Additionally, following one-limb training, capillary growth 4 and increased resting blood flow 20 was observed in the passively moved 4 and in the untrained limb. 4,20 This is the first study that monitored blood perfusion of back muscles in SCI during ACE.…”
Section: Muscle Perfusion During Arm Exercisementioning
confidence: 98%